Interactions between citizen responsibilization, flood experience and household resilience: insights from the 2013 flood in Germany. Issue 4 (4th July 2017) - Begg, Chloe; Ueberham, Maximilian; Masson, Torsten; Kuhlicke, Christian
Abstract: As increasing emphasis is placed on the importance of citizens' taking responsibility for their own preparedness and protection against flooding, it is important to understand the relationship between responsibility and action and how current practices of responsibilization influence household resilience. Based on a survey of 889 households affected by flooding in 2013 in the states of Saxony and Bavaria, Germany, this study investigates the relationship between action and flood experience and how this experience influences whether citizens feel responsible, and therefore the likelihood that they will take action in the future. These findings have implications for household resilience as well as future research.